PENGARUH SIKAP DAN INTENSITAS PENGGUNAAN FASILITAS PENDUKUNG BELAJAR TERHADAP HASIL BELAJAR MATA KULIAH LABORATORIUM AKUNTANSI (Survei pada Program Studi Pendidikan Ekonomi FIPPS Universitas Indraprasta PGRI) - Setiawati, Nur Amega (Universitas Indraprasta PGRI, 2015)
Abstract : The research aims to know about: (1) the regression of attitudes with to learning outcomes; (2) the regression of intensity of the use of learning facilities with the learning outcomes; (3) the regression of the two variables, namely the attitude and intensity of use of the facilities of learning with learning outcomes.The research was done in Universitas Indraprasta. The method of this research isquantitative description approach. The purpose of using this method was toanalyze the regression between two or more variable through hypotheses test and also to research social phenomena in real situation. From the research result, it can be concluded that if attitude, of the students did not significantly affect the study results. The same thing happens to the intensity of the use of learning facilities. turns student learning outcomes are influenced by other factors.nfluenced by other factor.Key words: attitude, facilities, and lerarning outcomes.